2013
DOI: 10.1088/1674-1056/22/1/010701
|View full text |Cite
|
Sign up to set email alerts
|

Orange dye—polyaniline composite based impedance humidity sensors

Abstract: This study presents the fabrication and investigation of humidity sensors based on orange dye (OD) and polyaniline (PANI) composite films. A blend of 3 wt.% OD with 1 wt.% PANI was prepared in 1 ml water. The composite films were deposited on glass substrates between pre-deposited silver electrodes. The gap between the electrodes was 45 μm. The sensing mechanism was based on the impedance and capacitance variations due to the absorption/desorption of water vapor. It was observed that with the increase in relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…M.T.S. Chani et al Studied the humidity sensitivity of an orange dye PANI composite film by impedance measurements and have showed a uniform change in impedance for humidity values ranging from 30 -90 % RH [17]. Room temperature humidity sensing of PANI-PVA composite has been studied by Y. Li and others, and they showed that the sensitivity of the composite increases with increased impedance from 10 -90 % RH and has both quick response and recovery times [18].…”
Section: Introductionmentioning
confidence: 99%
“…M.T.S. Chani et al Studied the humidity sensitivity of an orange dye PANI composite film by impedance measurements and have showed a uniform change in impedance for humidity values ranging from 30 -90 % RH [17]. Room temperature humidity sensing of PANI-PVA composite has been studied by Y. Li and others, and they showed that the sensitivity of the composite increases with increased impedance from 10 -90 % RH and has both quick response and recovery times [18].…”
Section: Introductionmentioning
confidence: 99%
“…Orange dyedoped PANI-based impedance sensor in the relative humidity range of 30-90% showed a uniform impedance-humidity relationship. Furthermore, annealed samples showed an increase in the sensitivity [31]. However, the low electrical conductivity and reversible humidity sensing effect of PANI at high humidity conditions hindered its practical use.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, annealed samples showed an increase in the sensitivity. 31 However, the low electrical conductivity and reversible humidity sensing effect of PANI under high humidity conditions hindered its practical use. Also, PANI sensors display poor reproducibility and stability upon repeated exposure to humidity.…”
Section: Introductionmentioning
confidence: 99%
“…Depending upon the nature of materials these sensors may be expansive or require high operational power/temperature and high cost of maintenance [3]. To make the sensor suitable for commercialization; the wide range sensitivity, linear response, small hysteresis, short response and recovery time, low cost and low power along with long term physical and chemical stability are the required characteristics [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the properties can be changed by changing of the ratio of ingredients in the composite. On the other hand the ingredients should be compatible in order to fabricate stable samples, i.e., to avoid the significant degradation processes [4,7]. Similarly, investigation of temperature variation effects to electric parameters of the materials are important for better understanding of mechanism of conduction, presence of phase transformation and application of the materials in temperature sensors for potential use in practice [8][9][10].…”
Section: Introductionmentioning
confidence: 99%